Urinary iron loss in the nephrotic syndrome–an unusual cause of iron deficiency with a note on urinary copper losses. Issue 700 (February 1984) - Brown, E. A.; Sampson, B.; Muller, B. R.; Curtis, J. R.
Abstract : Two patients with long-standing nephrotic syndrome are described in whom urinary iron losses may have contributed towards an iron deficiency state. Seven other nephrotic patients were also studied. Increased urinary iron excretion was found in six out of nine patients and increased urinary copper excretion in all eight patients in whom it was measured. Trace metal losses in the urine in nephrotics may be important clinically.